Pathohistological features of mediastinal lymphoma in domestic cats - Oriekhova, K.; Shchebentovska, O. (Regulatory Mechanisms in Biosystems, 2022)
The article covers two clinical cases of domestic cats suffering from a mediastinal form of lymphoma and provides their cytological, immunohistochemical, and pathohistological verification. The lymphoma immunophenotyping method using the B-cell markers CD79a and CD3 was used to identify T-cells. The mediastinal type of lymphoma in cats is usually rarely registered and statistically, the number of cases does not exceed 20%, which is consistent with our observations. Shortness of breath, difficulty with swallowing, lack of appetite, cyanotic mucous membranes, lymphadenomegaly of the mediastinal lymph nodes and effusion in the chest cavity were found in the clinically ill cats. An X-ray examination of the chest cavity revealed an increased contrast in the mediastinal area and displacement of the lungs towards the spine. A complete blood count revealed lymphopenia. Cytological smears of the chest cavity transudates revealed mostly monomorphic lymphoblasts with large rounded hyperchromic nuclei and narrow cytoplasm stained in light blue. The karyoplasm was somewhat granular, the nucleoli were visible, and the mitoses were atypical and numerous. The cytological picture in biopsy samples of mediastinal lymph nodes was characterized by a monomorphic population of lymphoblasts with an eccentrically located nucleus and moderately basophilic karyoplasm. The cell cytoplasm was vacuolated in some places, with presence of atypical mitotic figures. Most of the cells had two nuclei. Diffuse tumoral lesions of the chest cavity tissues, focal tumorous lesions of the lung parenchyma, and lymphadenopathy of the mediastinal lymph nodes were found during the autopsy in the first case. The second clinical case demonstrated the massive lymphadenopathy of the mediastinal lymph nodes. Histologically, a diffuse lesion by a monomorphic population of lymphoblasts was revealed in preparations from the soft tissues of the chest wall. The lymphoblasts’ insignificant cytoplasm, with nuclei from round to elliptical shape, infiltrated the chest wall’s soft tissues. It was found immunohistochemically that the blast cells showed reactivity to CD79a, and were mostly negative to CD3. This indicates the development of a large diffuse B-cell lymphoma. The immunohistochemical picture of lymph node necropsies from another cat was somewhat similar. However, it was also characterized by lymphoblasts with eccentrically placed nuclei, increased number of cells with mitotic figures, somewhat intensive CD3 antibodies expression (especially in the paracortical area of lymph nodes), and significant CD79a marker expression.